Philosophic whigs : medicine, science, and citizenship in Edinburgh, 1789-1848 - Jacyna, L. S. (Wellcome Institute series in the history of medicine., 1994)
In this fascinating study of the Edinburgh medical school in the early nineteenth century, L.S. Jacyna analyses the developments in medical education in the context of the social and political relationships within the local Whig community.